2009
DOI: 10.1007/s11199-009-9609-5
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction and Disordered Eating Among Early Adolescents From Korea and the US

Abstract: Multidimensional measures of body dissatisfaction and disordered eating were studied in samples of 12-15 years old middle school children. Consistent with feminist theories associating body dissatisfaction with rapid social change, Korean girls (n=272) exhibited the greatest body dissatisfaction and the most behaviors associated with disordered eating and were followed in order by Korean boys (n=276), US girls (n=251), and US boys (n=220). The results, which replicated Jung and Forbes (2006) report of greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 68 publications
(77 reference statements)
2
46
0
1
Order By: Relevance
“…Despite the evidence that rates of cosmetic surgery in South Korea have increased sharply in the past decade, much of the available research continues to document rates of specific procedures (e.g., McCurdy and Lam 2005) rather than to examine individual or socio-cultural factors influencing cosmetic surgery procedures. According to the empirical evidence, South Korean women and girls have greater body dissatisfaction than women and girls in the United States (e.g., Forbes and Jung 2008;Jung et al 2009). A study by Jung and Forbes (2006) suggests that women in cultures such as South Korea, where increased opportunities for women produced a marked shift toward gender equality, are likely to experience increased pressures to conform to unrealistic appearance standards.…”
Section: Open Accessmentioning
confidence: 99%
“…Despite the evidence that rates of cosmetic surgery in South Korea have increased sharply in the past decade, much of the available research continues to document rates of specific procedures (e.g., McCurdy and Lam 2005) rather than to examine individual or socio-cultural factors influencing cosmetic surgery procedures. According to the empirical evidence, South Korean women and girls have greater body dissatisfaction than women and girls in the United States (e.g., Forbes and Jung 2008;Jung et al 2009). A study by Jung and Forbes (2006) suggests that women in cultures such as South Korea, where increased opportunities for women produced a marked shift toward gender equality, are likely to experience increased pressures to conform to unrealistic appearance standards.…”
Section: Open Accessmentioning
confidence: 99%
“…For example, in a study comparing levels of overall body dissatisfaction in male and female adolescents from Korea and the United States, Jung et al (2009) found that Korean boys and girls reported significantly greater body dissatisfaction than their U.S. counterparts. However, as Swami and Chamorro-Premuzic (2008) argued, there may be cross-cultural differences in the variables contributing to body image and body dissatisfaction.…”
Section: Male Body Dissatisfaction Across Western and Asian Culturesmentioning
confidence: 99%
“…For example, gender differences in body dissatisfaction have been documented among Western adolescents including American 13-19 year olds (e.g., Ata et al 2007;Jones and Crawford 2006), 11-17 year old Australians (Vincent and McCabe 2000), French 16 year olds (e.g., Rodgers et al 2009), Irish 12-18 year olds (Lawler and Nixon 2011), and Swiss 14-16 year olds (e.g., Knauss et al 2008). Such differences extend to adolescents in Asian nations including 12-15 year olds in South Korea (Jung et al 2009) and 12-19 year olds in mainland China (Chen and Jackson 2009;Chen et al 2006;Xie et al 2006).…”
Section: Introductionmentioning
confidence: 95%